Chronic Pain and Fatigue: Associations with Religion and Spirituality - Marilyn Baetz; Rudy Bowen (Pain Research and Management)
BACKGROUND: Conditions with chronic, non-life-threatening pain and fatigue remain a challenge to treat, and are associated with high health care use. Understanding psychological and psychosocial contributing and coping factors, and working with patients to modify them, is one goal of management. An individual’s spirituality and/or religion may be one such factor that can influence the experience of chronic pain or fatigue.